Joint meeting on short rotation forestry (1999)
The objectives of the meeting were to: assemble environment researchers, specialist to discuss framework of future projects, networking and joint education exchange, gather information on the present environment situation of each member's country, and encourge interraction among environment experts, specialists, researchers and professionals concerned on environment mangement.